Refitalisasi Peran Keluarga Sebagai Basis Perlindungan Anak Perspektif Fikih Munakahat - Muhammad Najib Asyrof (ABHATS: Jurnal Islam Ulil Albab, 2020)
Almost two decades of socialization on Child Protection have been socialized in Indonesia, but there are still many violations of the fundamental rights of children. The family should be the first place for children to be safe and comfortable; instead, it becomes a worrying place. This research is expected to offer a concept of Child Protection by tracing back the meaning of child protection so that it can be translated by the wider community and especially families in Indonesia comprehensively so that it becomes a child-friendly society.This qualitative study focuses on a literature review using a normative approach to rehabilitate and make a positive contribution to the child protection movement that is not yet optimal, especially during the Covid-19 pandemic with a more specific and thoughtful approach, namely fiqh munakahat (marriage). This study resulted in an alternative definition of Child Protection, namely a continuous effort to create a conducive atmosphere for children to carry out their fundamental rights and obligations rationally, responsibly, and beneficially, starting from the moment parents choose a life partner and avoid violence and discrimination. The first step in protecting children from the fiqh munakahat perspective that can be done is selective in choosing a life partner, starting with paying attention to aspects of commitment to carrying out religious orders, morals, and the environment for growth and development of prospective partners, building a family on a valid marriage, and avoiding marriages that have close kinship.